IMPLEMENTASI SUPERVISI KELAS KEPALA SEKOLAH DALAM PENINGKATAN KINERJA GURU SEKOLAH DASAR - Indhi Kriswati; Rahmat Rahmat (PEDIR: Journal of Elementary Education, 2022)
Educational supervision is a very important activity to be implemented in schools. Transcendentally the principal as a supervisor is someone who supervises and provides assistance to teacher performance to improve the learning process so that it fits thelearning objectives. The role of the principal as a supervisor in improving teacher performance. Therefore, the principal's strategy in improving teacher performance is important in education. This study aims to find out 1) To describe the planning of the principal's class supervision program in improving teacher performance at SD Negeri Plabuhan III, Plandaan District, Jombang Regency. 2) To identify the implementation of the principal's class supervision program in improving teacher performance at SD NegeriPlabuhan III, Plandaan District. Jombang Regency. 3) To identify the evaluation and 4) To identify follow-up of the principal's supervision program in improving teacher performance at SD Negeri Plabuhan III, Plandaan District, Jombang Regency. This research used a qualitative method with a case study approach. The data collection techniques of this research were observation, interviews and documentation. The results of this study showed that: Supervision planning, namely: 1) meetings, 2) supervision socialization, procurement of learning tools 3) making schedules 4) dividing schedules and supervision tools. The implementation of the program has been communicated properly 1) Empowerment of meetings, 2) completion of procurement of learning tools, 3) making schedules, and 4) realization of sharing schedules and supervision tools. The results are 1) meetings, 2) socialization of supervision, procurement of learning tools 3) making schedules 4) dividing schedules and analyzing supervision tools. This research investigated 1) meetings, 2) socialization of the supervision of the procurement of learning tools, 3) making a schedule 4) dividing the schedule and supervision tools for post-supervision activities to reflect on the results of the supervision that has been carried out.